Megiddo in the Middle Bronze Age: chronology, urbanization, and population - Adams, Matthew J.; Martin, Mario A. S.; Dunseth, Zachary C.; Yasʿur-Landau, Assaf; Finḳelshṭayn, Yiśraʾel (Near Eastern archaeology, 2025)
This article deals with Middle Bronze Megiddo, emphasizing its importance for understanding this period at the site, and in the entire southern Levant in general. We focus on new evidence for exceptional accumulation of layers for the earliest Middle Bronze layer, radiocarbon dated to the early twentieth century BCE, and for the first fortification system also dated to the twentieth century BCE. We also deal with the complex history of the fortifications, including gates, and the phenomenon of intramural burials, some of them of monumental nature., PLEASE NOTE: This article contains images of human skeletal remains., SIDEBAR P. 144: The Mortuary Record of Area K, by Rachel Kalisher, SIDEBAR P. 146: DNA Analysis of Megiddo Individuals, by Lily Agranat-Tamir and Liran Carmel